2017
DOI: 10.2147/bctt.s131407
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy detecting alterations of upper limb lymphatic flow following early sentinel lymph node biopsy in breast cancer

Abstract: PurposeTo evaluate early variations in lymphatic circulation of the arm pre- and post-sentinel lymph node biopsy (SLNB) and conservative breast surgery by lymphoscintigraphy (LS).Patients and methodsBetween 2005 and 2012, 15 patients underwent LS before and after the SLNB (total=30 studies). The pre-SLNB study was considered the control. Early images within twenty minutes (dynamic and static images) and delayed images within ninety minutes of arms and armpits were acquired using a gamma camera. The LS images b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Lymphoscintigraphy is the primary imaging modality used in determining the diagnosis of suspected extremity lymphedema in patients. Lymphoscintigraphy, magnetic resonance imaging (MRI), and lymphangiography findings in patients with lymphedema show interruption of lymphatic flow, collateral lymph vessels, dermal back flow, delayed flow, delayed visualization or non-visualization of lymph nodes (LNs), dilated lymphatics, and no visualization of the lymphatic system [3][4][5][6][7][8][9]. When collateral LVs bridging the distal LV (over the area of lymphadenectomy) to the proximal LV or to the remaining LNs with LVs are observed in patients using lymphoscintigraphy (at the area of the lymphadenectomy), lymphedema is said to be mild or moderate [3,5,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphoscintigraphy is the primary imaging modality used in determining the diagnosis of suspected extremity lymphedema in patients. Lymphoscintigraphy, magnetic resonance imaging (MRI), and lymphangiography findings in patients with lymphedema show interruption of lymphatic flow, collateral lymph vessels, dermal back flow, delayed flow, delayed visualization or non-visualization of lymph nodes (LNs), dilated lymphatics, and no visualization of the lymphatic system [3][4][5][6][7][8][9]. When collateral LVs bridging the distal LV (over the area of lymphadenectomy) to the proximal LV or to the remaining LNs with LVs are observed in patients using lymphoscintigraphy (at the area of the lymphadenectomy), lymphedema is said to be mild or moderate [3,5,7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Sarri et al [47] evaluated early variations in lymphatic circulation of the arm pre-and post-SLNB and conservative breast surgery by means of lymphoscintigraphic study. They concluded that, although further studies are needed to confirm their findings, monitored by lymphoscintigraphy, upper limb lymphatic flow gradually decreased after an SLNB.…”
Section: Main Applications Of Lymphoscintigraphy In the Sentinel Lympmentioning
confidence: 99%